Wzrost gospodarczy a optymalne zróżnicowanie dochodów w USA i Szwecji - Pawlak, Witold; Sztaudynger, Jan Jacek (Annales. Etyka w Życiu Gospodarczym, 2008)
Inequality of incomes is one of the significant factors forming the social capital. Two views dominate among economists dealing with the influence of inequality of income on economic growth. On the one hand, a too low inequality of income does not motivate people to increase the labour productivity. A low inequality of income might result from an extended social care system and overloading GDP with social transfers. A good example of it may be a situation when the unemployed refuses to accept a job offer and prefers the unemployment benefit rather to a slightly higher salary. Moreover, a lack of incentives for the employee who fails to acknowledge the economic sense of increasing the productivity of his work might lead to the slower growth of economy. On the other hand, a contrary view suggests that an increase of the inequality of income has a negative impact on the economy. The accumulation of wealth by a small number of citizens raises doubts about good use of that wealth for investments necessary for the growth of the economy. An excessive inequality of income is confronted with disapproval of the significant part of society and regarded as unfair and unjustified. It may also increase the crime level and decrease the trust and, more generally, lead to the weakening of social capital. The arguments above lead to a hypothesis that the influence of the inequality of income on the growth of the economy has a non-linear character. We confirmed this hypothesis in growth models of the US and Swedish economies. We assess the historically optimal inequality of income measured by the Gini coefficient at 46% and 24% for the US and Sweden respectively. The optimal inequality of income in Poland was assessed previously at 29%. The dissimilarities may result from the cultural differences, educational level differences, ethnic differences and differences in diligence.